A communicative grammar of English - Leech, Geoffrey; Svartvik, Jan. (New York : Longman, 2001)
A fully updated version of the highly successful Advanced grammar in use - extra practice is also available on a new interactive CD-ROM to accompany the book. This is the edition with answers.
Includes index.
Keywords: English language -- Grammar -- Problems, exercises, etc; Language; English language -- Grammar